The role of BRCA1/2 in hereditary and familial breast and ovarian cancers - Hawsawi, Yousef M. (Mol Genet Genomic Med, 2019)
BACKGROUND: BRCA1/2 pathogenic variants have become associated with familial breast and ovarian cancers, and hereditary cancer‐predisposition syndrome. With advances in molecular biology, BRCA profiling facilitates early diagnosis and the implementation of preventive and therapeutic strategies. The genes exhibit variable prevalence among different individuals and moderate interpretation complexity. BRCA deficiency is instrumental in cancer development, affects therapeutic options and is instrumental in drug resistance. In addition, BRCA1/2 profile is diverse across different groups and has been associated with the “founder effect” in certain populations. METHODS: In this review, we aim to detail the spectrum of BRCA1/2 variants and their associated risk estimates. RESULTS: The relationship between BRCA1/2 and hereditary and familial cancers is indisputable, yet BRCA screening methods are beset with limitations and lack clinical confidence. CONCLUSION: This review emphasizes the importance of screening BRCA genetics, in addition to their clinical utility. Furthermore, founder variants are anticipated in the Saudi population.